1996
DOI: 10.1207/s15327108ijap0602_2
|View full text |Cite
|
Sign up to set email alerts
|

Review of Psychomotor Skills in Pilot Selection Research of the U. S. Military Services

Abstract: This review provides an historical perspective of the use of psychomotor, perceptual--cognitive paper-and-pencil, and automated tests for the selection of pilot trainees by the U.S. military services. Automated versions of vintage psychomotor tests (developed in the 1930s and 1940s) seem to be as predictive of military pilot/aviator performance today as in the past. The psychomotor tests receiving the most attention today are the Complex Coordination and Two-Hand Coordination tests originally developed by Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 17 publications
0
24
0
3
Order By: Relevance
“…In fact, interindividual variability in sensory-guided motor behavior abilities has been utilized across a great number of studies aimed at understanding what factors contribute to greater or lesser achievement in different applied settings. The results of these studies indicate that better perceptual and visual-motor skills are predictive of success in a number of important endeavors, including industrial job performance (Hunter, 1986;Hunter & Hunter, 1984), military duties (Griffin & Koonce, 1996;Johnston & Catano, 2002;King et al, 2013), and surgical performance (Datta et al, 2002;Maan, Maan, Darzi, & Aggarwal, 2012). In a similar vein, two recent meta reviews of the sports expertise literature demonstrate that certain visual-perceptual abilities are enhanced in more accomplished athletes, relative to less accomplished athletes (Mann, Williams, Ward, & Janelle, 2007;Voss, Kramer, Basak, Prakash, & Roberts, 2010).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…In fact, interindividual variability in sensory-guided motor behavior abilities has been utilized across a great number of studies aimed at understanding what factors contribute to greater or lesser achievement in different applied settings. The results of these studies indicate that better perceptual and visual-motor skills are predictive of success in a number of important endeavors, including industrial job performance (Hunter, 1986;Hunter & Hunter, 1984), military duties (Griffin & Koonce, 1996;Johnston & Catano, 2002;King et al, 2013), and surgical performance (Datta et al, 2002;Maan, Maan, Darzi, & Aggarwal, 2012). In a similar vein, two recent meta reviews of the sports expertise literature demonstrate that certain visual-perceptual abilities are enhanced in more accomplished athletes, relative to less accomplished athletes (Mann, Williams, Ward, & Janelle, 2007;Voss, Kramer, Basak, Prakash, & Roberts, 2010).…”
Section: Introductionmentioning
confidence: 92%
“…Because these tasks all rely on rapid and accurate processing of distributed visual information and subsequent motor responses, this factor was interpreted as reflecting 'Visual-Motor Control' abilities. Previous research on human psychomotor abilities has frequently identified Visual-Motor Control to be among the latent factors underlying human performance (e.g., Chaiken et al, 2000) that are also among the most significant predictors of real-world outcomes (Griffin & Koonce, 1996;Hunter & Hunter, 1984).…”
Section: Factor Structure Of Perceptual and Visual-motor Abilities Asmentioning
confidence: 99%
“…Psychomotor skills research has a long history in pilot selection (Griffin & Koonce, 1996). The term 'psychomotor' denotes a combination of physical and psychological activities (Plug et al, 1989).…”
Section: Psychomotor Coordinationmentioning
confidence: 99%
“…Griffin ve Koonce [9] araştırmalarında, Amerika Birleşik Devletleri askeri pilot adaylarının seçimi için psikomotor, algısal-bilişsel kâğıt-kalem ve bilgisayar testlerinin kullanımına ilişkin tarihsel bir inceleme yapmıştır. Kantor ve Caretta [10], askeri pilot adaylarının seçilmesinde psikomotor ve bilişsel testlerin bilgisayar bataryasını geliştirmek ve geçerliliğini denetlemek için bir çalışma yürütmüştür.…”
Section: Introductionunclassified